Biomethane Potential of Selected Organic Waste and Sewage Sludge at Different Temperature Regimes - German Smetana; Ewa Neczaj; Anna Grosser (Energies, 2021)
Sewage sludge (SS) generation and its management still pose a problem in many countries. Anaerobic co-digestion (AcD) of SS with grease trap sludge (GTS) and organic fraction of municipal sewage waste (OFMSW), which are two easily biodegradable substrates, may improve biogas production and AcD kinetics. Algae biomass (AB) of the species Undaria pinnatifida can be the third co-digestion component that may also affect the AcD performance. The aim of the study was therefore to evaluate the performance of mesophilic and thermophilic SS batch AcD with OFMSW, GTS as well as AB through biochemical methane potential (BMP) assay in relation to cumulative specific biogas (YB) and methane yields (Ym). Three kinetic models were applied within the scope of the kinetic study. Results of the study showed that the mixture containing SS, GTS and AB brought the most noticeable improvements in Ym compared to other studied mixtures and in respect to standalone SS digestion, the improvement amounted to 88.37% at mesophilic temperature (260.83 ± 15.02 N mL CH4/g-VSadd and for standalone SS 138.47 ± 4.70 N mL CH4/g-VSadd) and 71.09%, respectively, at the thermophilic one (275.66 ± 4.11 N mL-CH4/g-VSadd and for SS standalone 161.13 ± 13.11 N mL-CH4/g-VSadd).